2013
DOI: 10.4314/wsa.v39i5.4
|View full text |Cite
|
Sign up to set email alerts
|

Detection and confirmation of toxigenic <i>Vibrio cholerae</i> O1 in environmental and clinical samples by a direct cell multiplex PCR

Abstract: Epidemic cholera caused by toxigenic Vibrio cholerae O1 is a major health problem in several developing countries. Traditional methods for identifying V. cholerae involve cultural, biochemical and immunological assays which are cumbersome and often take several days to complete. In the present study, a direct cell multiplex PCR was developed targeting the ompW, ctxB and rfbO1 genes for confirmation of V. cholerae, its toxigenicity and serogroup O1, respectively from clinical and environmental samples. The dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
(6 reference statements)
1
6
0
Order By: Relevance
“…Similar results were also reported in 2013, 2015 and 2016 [86]- [89]. The presented findings agree with result published in 2007 [90] which revealed that all strains tested in multiplex PCR analysis showed positive for ace, ctxB, hlyA, ompU, ompW, rfbO1, rtx, tcpA, toxR and zot virulence genes.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Similar results were also reported in 2013, 2015 and 2016 [86]- [89]. The presented findings agree with result published in 2007 [90] which revealed that all strains tested in multiplex PCR analysis showed positive for ace, ctxB, hlyA, ompU, ompW, rfbO1, rtx, tcpA, toxR and zot virulence genes.…”
Section: Discussionsupporting
confidence: 82%
“…On the other hand, all the isolated 35 Vibrio were positive for the ompW gene. The ompW gene acts as an internal control for V. cholera and could be compatible with the biochemical and serological tests which are used to identify the suspects Vibrio isolate [91], which plays an important role in the physiology of these bacteria and has an impact on the rapid adaptation of the bacteria to the environment [92] representing a species-specific for V. cholera [86].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, lack of required facilities in small laboratories in remote areas makes the detection of organism difficult. In addition, there are some molecular methods for the detection of toxigenic V. cholerae , with high sensitivity and specificity [ 3 , 4 ]. However, these methods have two fundamental problems: (1) they are expensive and require laboratory facilities and trained personnel and (2) presence of a gene coding exotoxin does not necessarily prove the production and secretion of the relevant protein.…”
Section: Introductionmentioning
confidence: 99%
“…Even though up to 80% of the cases can be successfully treated with oral rehydration salts [ 19 ], the high death rates indicate that early and rapid detection of the cholera is necessary to prevent spread of disease and to decrease the intensity of epidemics. Traditional methods to identify V. Cholerae involving culture, biochemical, and immunological assays are time-consuming and laborious [ 16 , 20 ]. There are commercially available rapid detection tests such as the SMART TM test [ 21 24 ] and the Crystal VC ® dipstick test [ 24 27 ].…”
Section: Introductionmentioning
confidence: 99%